Effect of a comprehensive programme to provide universal access to care for sputum-smear-positive multidrug-resistant tuberculosis in China: a before-and-after study. Issue 4 (April 2015) - Li, Renzhong; Ruan, Yunzhou; Sun, Qiang; Wang, Xiexiu; Chen, Mingting; Zhang, Hui; Zhao, Yanlin; Zhao, Jin; Chen, Cheng; Xu, Caihong; Su, Wei; Pang, Yu; et al.
Summary: Background: China has a quarter of all patients with multidrug-resistant tuberculosis (MDRTB) worldwide, but less than 5% are in quality treatment programmes. In a before-and-after study we aimed to assess the effect of a comprehensive programme to provide universal access to diagnosis, treatment, and follow-up for MDRTB in four Chinese cities (population 18 million). Methods: We designated city-level hospitals in each city to diagnose and treat MDRTB. All patients with smear-positive pulmonary tuberculosis diagnosed in Center for Disease Control (CDC) clinics and hospitals were tested for MDRTB with molecular and conventional drug susceptibility tests. Patients were treated with a 24 month treatment package for MDRTB based on WHO guidelines. Outpatients were referred to the CDC for directly observed therapy. We capped total treatment package cost at US$4644. Insurance reimbursement and project subsidies limited patients' expenses to 10% of charges for services within the package. We compared data from a 12 month programme period (2011) to those from a retrospective survey of all patients with MDRTB diagnosed in the same cities during a baseline period (2006–09). Findings: 243 patients were diagnosed with MDRTB or rifampicin-resistant tuberculosis during the 12 month programme period compared with 92 patients (equivalent to 24 per year) during the baseline period. 172 (71%) of 243 individuals were enrolled in the programme. Time from specimen collection for resistance testing to treatment initiation decreased by 90% (from median 139 days [IQR 69–207] to 14 days [10–21]), the proportion of patients who started on appropriate drug regimen increased 2·7 times (from nine [35%] of 26 patients treated to 166 [97%] of 172), and follow-up by the CDC after initial hospitalisation increased 24 times (from one [4%] of 23 patients to 163 [99%] of 164 patients). 6 months after starting treatment, the proportion of patients remaining on treatment increased ten times (from two [8%] of 26 patients to 137 [80%] of 172), and 116 (67%) of 172 patients in the programme period had negative cultures or clinical–radiographic improvement. Patients' expenses for hospital admission after MDRTB diagnosis decreased by 78% (from $796 to $174), reducing the ratio of patients' expenses to annual household income from 17·6% to 3·5% (p<0·0001 for all comparisons between baseline and programme periods). However, 36 (15%) patients did not start or had to discontinue treatment in the programme period because of financial difficulties. Interpretation: This comprehensive programme substantially increased access to diagnosis, quality treatment, and affordable treatment for MDRTB. The programme could help China to achieve universal access to MDRTB care but greater financial risk protection for patients is needed. Funding: Bill & Melinda Gates Foundation .